Silviculture treatments and age on growth and wood properties of naturally regenerated Acacia mangium Willd. in Kemasul Forest Reserve, Pahang, Malaysia - Kassim, Amir Sariffudin (2013)
High planting cost and labor shortages was the main problem in new plantation establishment. Natural regeneration is an attractive method for establishment of second rotation Acacia mangium stand. However, the management procedure of this stand needs to be established to avoid risk of using inappropriate silvicultural strategies. The objective of this study is to determine the best timing for first thinning, to study the effect of stand density and to determine the wood specific gravity of four and five year old stand after one year of the first thinning. This study was conducted in two - four years old naturally regenerated A. mangium stands at Kemasul Forest Reserve, Pahang. The trial consists of three replicates and twelve treatments of 0.09 ha (30 x 30 m) plots aged two, three and four years. The total number of plots: 36 and total research area covers 3.24 ha. Selective . low thinning concepts with the retention of most vigorous individual trees were used for crop trees selection although it was selected as evenly spaced as possible. Mean annual diameter at breast height (DBH) increment for thinning at age three (3.1 cm year") shows significantly higher differences (p<O.OS) compared to thinning at age two (2.4 cm year") and four (2.9 cm year") years. DSH increment for 600 stems ha" was significantly larger at 3.8 cm year", Mean height increment however, does not shows significant difference between thinning treatments. Thinning the naturally regenerated A. mangium stand at age three also shows significantly larger basal area (0.06 m2 tree") and volume (0.07 m3 tree") increments between aU age classes. Periodic annual increment (PAl) data from stand and stock tables shows that plot TS produces greatest DSH (4.8 cm) and basal area (3.4 m2 ha-1 ) increments. Largest periodic annual volume increment (PAlv) was from T7; (42.5 m3 ha"). Mean increment of wood specific gravity (SG) from pith to bark was 31%. The variation in the mean SG value however, was not significant at p<0.0001 between the different stand age, thinning treatments and the interaction of both age and thinning treatment. To create uniform regenerated stands and to avoid root diseases, establishment work which includes stacking and burning is proposed. In areas with low regeneration rates, direct sowing and refilling can also be practice. Thinning treatment in the naturally regenerated A. mangium stand should be done at age three years. Preliminary growth, yield and wood properties result from this trial would help researchers to identify processes that control productivity and future prediction of timing for the final harvest.